Two interacting X lines in magnetotail: Evolution of collision between the counterstreaming jets - Alexandra Alexandrova; Rumi Nakamura; Evgeny V. Panov; Yury L. Sasunov; Takuma Nakamura; Zoltán Vörös; Alessandro Retinò; Vladimir S. Semenov (Geophysical Research Letters)
Abstract We study the process of collision between the counterstreaming jets flowing out from two reconnection sites in the Earth's magnetotail. The X lines, bracketing the region of jets collision, were passing by two Cluster probes successively in tailward direction. Two probes observed two different stages of the collision process. At the jets collision site, a probe first observed an ion‐scale current sheet‐like structure, while the other probe observed more compressed one later. The strong wave activities on both ion and electron scales were seen within the compressed layer. Such evolution of the jets collision resulting in the formation of the compressed boundary between the active X lines shows an example of interaction between the X lines during multiple reconnection.